DINAMIKA KESENIAN WAYANG KULIT DI KOTA LANGSA - madhan anis; Choiriah Choiriah (Program Studi Pendidikan Sejarah - Universitas Samudra, 2019)
Art is one element of culture. One form of the art is wayang kulit. Wayang kulit is one of several traditional Javanese arts. In its development from time to time, wayang has undergone changes in accordance with the development of the supporting community. Puppet has passed various historical events from generation to generation. So that the culture of wayang has been attached to the Indonesian people, especially the Javanese people. Along with the spread of the Javanese community to almost all parts of Indonesia, one of them in Aceh, a lot of activities of migrant communities, especially the Javanese tribe in Aceh, did not leave the art of their ancestors, one of which was shadow puppets. This is certainly something unique if an art is able to develop or survive in an area that is far from its roots and able to adapt to its new place.